Removal of humic acid from aqueous solution using MgO nanoparticles - Rasuli Leila; Mahvi Amir Hossein (Химия и технология воды, 2016)
The main purpose of this work was to investigate the removal of humic acid (HA) from aqueous solutions using MgO nanoparticles as a novel adsorbent. The effect of contact time, competing anions in the aqueous solutions, for the removal of HA in batch system was studied. The nanoparticle was characterized by scanning election microscope method. Experimental results show that MgO nanoparticles can remove more than 90% of HA under optimum conditions. The results showed that the examined interfering anions influenced the HA removal. The adsorption kinetics and isotherm were also studied. The adsorption kinetics was well described by the pseudo-second-order equation, and the adsorption isotherms were better fitted by the Langmuir model.